2020
DOI: 10.1111/cas.14370
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus‐positive gastric cancer involves enhancer activation through activating transcription factor 3

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractEpstein-Barr virus (EBV) is associated with particular forms of gastric cancer (GC).We previously showed that EBV infection into gastric epithelial cells induced aberrant DNA hypermethylation in promoter regions and silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…EBV infection causes enhancer activation and repression, which may be associated with gastric carcinogenesis [31]. A recent study suggested that enhancer activation through ATF3 might be involved in carcinogenesis [32]. Our latest study has revealed that interaction of episomal EBV genome may directly rewire the host chromatin structure to aberrantly activate proto-oncogenes and promote gastric carcinogenesis [17].…”
Section: Epigenetic Aberrant In Gastric Cancermentioning
confidence: 99%
“…EBV infection causes enhancer activation and repression, which may be associated with gastric carcinogenesis [31]. A recent study suggested that enhancer activation through ATF3 might be involved in carcinogenesis [32]. Our latest study has revealed that interaction of episomal EBV genome may directly rewire the host chromatin structure to aberrantly activate proto-oncogenes and promote gastric carcinogenesis [17].…”
Section: Epigenetic Aberrant In Gastric Cancermentioning
confidence: 99%
“…The dynamics of histone alterations usually cooperate with transcription programs to interact with genes through master transcription factors (TFs) by binding specific enhancer regions 21,22 . It has been reported that one of the master TFs, ATF3, induces aberrant enhancer activation after EBV infection in GC 23 . Other studies have also implied that EBV infection can induce enhancer rewiring by chromatin structural aberrations, contributing to EBV‐positive GC tumorigenesis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies indicated the complexity of gastric cancer exits in different subtypes such as Epstein-Barr virus (EBV), microsatellite instability (MSI), and so on [ 30 ]. In the study by Asakawa et al [ 31 ], upregulation of ATF3 is linked with aberrant enhancer activation in EBV infected gastric epithelial cells (e.g. SNU719 and NCC24), and enhances proliferation of these gastric cells.…”
Section: Discussionmentioning
confidence: 99%